Evaluation of role of laparoscopy in determining etiology of infertility - K. R., Hema; H. S., Lalitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Although population explosion is a major problem in India, infertility appears to be a problem in 5-15% of Indian population. All these patients require evaluation. Laparoscopy plays a valuable role in the diagnosis of infertility. After thorough clinical examination and specific investigations, diagnostic laparoscopy is performed to detect patency of tubes, morphological defects in uterus, ovaries and tuboperitoineal factors. This study was conducted to assess the role of diagnostic laparoscopy in the investigation of female infertility and to evaluate the various causes of infertility like endometriosis, PCOD tubal and peritoneal factors, uterine anomalies, tuberculosis etc. by using diagnostic laparoscopy. Methods: Study was carried out in 60 infertile patients attending outpatient department of hospitals attached to Sri Siddhartha Medical College Hospital, Tumkur. Both primary and secondary infertility patients who were anxious to conceive and undergo diagnostic laparoscopy were evaluated. Those who were not willing and who were contraindicated for the procedure were excluded. Results: Diagnostic laparoscopy was performed in 72% of primary and 28% of secondary infertility patients. Majority of the patients of primary infertility were in age group 21-25 years and that of secondary were between 26-30 years. Majority of patients in both the groups had duration of 1-5 year of infertility. In our study tubal factors (50%) contributed to majority of the infertility causes. Complication rate was minimum and was comparable to other standard studies. Conclusions: Laparoscopic is the gold standard for diagnosing tubal and peritoneal disease, endometriosis and other pelvic pathology, because no other imaging technique gives the same degree of sensitivity or specificity. Hence diagnostic laparoscopy is an indispensable tool in the evaluation in the evaluation infertility.